Investigation of brain tumour patients with headache and non-headache phenotypes using sequences of MRA, MRS and DWI techniques - Chandra, Changmai Manah (2022)
The sequences of proton magnetic resonance spectroscopy (MRS), magnetic resonance angiography and diffusion weighted imaging (DWI) play a vital role in recognizing the brain tumours with headache. MRS calculates the concentration of brain metabolites to determine the characteristics and grading of the brain tumour with headache. Diffusion weighted imaging evaluates the apparent diffusion coefficient (ADC) values depicting tissue heterogeneity and brain tumour cellularity depicting cause of headache. MRA is utilized to understand anatomy of intracranial blood vessels with aneurysm or stenosis in brain tumour headache. All these three techniques of magnetic resonance imaging are non-invasive techniques. The brain tumour initiates imbalance in the brain metabolism which is a factor for aneurysm of intracranial blood vessels precipitating headache. At the same time, increased cellularity of these tumours is another consideration for origin of headache. Thus this study aims to investigate the relation from impact of tumour associated changes in metabolites, caliber of the intracranial blood vessels and its cellularity causing headache. In this cross sectional study, retrospective HUSM 3T MRI radiological images of PRESS MRS, time-of-flight MRA and b0 and b-1000 s/mm2 DWI images from 2013 – 2018 years are selected. This includes 77 brain tumour patients with headache and 61 non-headache patients selected from PAC system and patient case files. Further, Patients with MRA, MRS and DWI were filtered for their respective analysis. Manual processing and software packages Radiant DICOM viewer (2020 2.3), Image J and Neuromantic v1.6.3 are applied by setting up ROI and different methods of estimation and analysis. The evaluation of brain metabolites, caliber of intracranial blood vessel and ADC values are statistically compared using SPSS software version 23. The results indicate a clear and wider picture of the alteration of metabolites providing information of the type and grading of tumour associated with headache. A drop in NAA level has illustrated involvement of the neurons and the rise in Cho level displayed increase membrane cellularity in tumour core of headache patients that corresponds with the low ADC value of (0.65±0.46 10-3 mm2/s) in tumour core depicting high cellularity of the tumour in headache patients precipitating headache. Consequently, a decrease in Cho/Cr ratio in contralateral healthy side of brain tumour patients with headache has imitated a typical tension type of headache. This is also supported by dilatation of ICA (5.03±1.40) in tumour side of headache patients compared to non-headache (3.31±1.81) brain tumour patient. The final results has established a connection between the changes in metabolites, increase cellularity and changes in the intracranial blood vessels enlightening the type of headache that provides valuable information to cure brain tumour patient with headache.